Fiscal Transparency in EU Accession Countries : Progress and Future Challenges - Allan, William (IMF Working Papers; Working Paper ;, 2003)
This paper discusses the findings of fiscal transparency reports on standards and codes (ROSCs) for most EU accession candidate countries. Emphasis is given to the need to establish effective and accountable medium-term budget frameworks to establish policy credibility and anchor adjustment programs to meet EU fiscal goals. Adoption of budgeting and accounting standards consistent with the IMF Government Finance Statistics Manual 2001 framework will also help link budget decisions to EU standards of fiscal reporting. More consistent and comprehensive coverage of off-budget activities is needed for assessing fiscal risk and sustainability. Finally, local government issues need to be addressed by many of these countries since EU fiscal goals are set with reference to general government. Progress in all of these areas can be monitored by keeping fiscal ROSC assessments up to date.